COVID‐19 vaccine controversy: A cross‐sectional analysis of factors associated with COVID‐19 vaccine acceptance amongst emergency department patients in New York City. Issue 6 (17th November 2022) - Guzman, Christina P.; Aron, Jamie; Egbebike, Jennifer; Greene, M. Claire; Reisig, Christopher; DeFilippo, Michael; Bollman, E. Brennan; Stefan, Bianca R.; Chang, Bernard P.; Wagh, Anju; Firew, Tsion
Abstract: Objective: Understanding variables associated with coronavirus disease 2019 (COVID‐19) vaccine confidence and hesitancy may inform strategies to improve vaccine uptake in clinical settings such as the emergency department (ED). We aim to identify factors contributing to COVID‐19 vaccine acceptance and to assess patient attitudes surrounding offering COVID‐19 vaccines in the ED. Methods: We conducted a survey of a convenience sample of patients and patient visitors over the age 18 years, who were native English or Spanish speakers. The survey was conducted from March through August 2021 at 3 EDs in New York City. The survey was administered via an electronic format, and participants provided verbal consent. Results: Our sample size was 377. Individuals with post‐graduate degrees viewed vaccines positively (Prevalence Ratio [PR], 1.63; 95% Confidence Interval [CI], 1.07–2.47). Of the various high‐risk medical conditions associated with adverse COVID‐19 infection outcomes, diabetes was the only condition associated with more positive views of vaccines (PR, 1.37; CI, 1.17–1.59). Of all participants, 71.21% stated that they believed offering a COVID‐19 vaccine in the ED was a good idea. Of unvaccinated participants, 21.80% stated they would get vaccinated if it were offered to them in the ED. Conclusion: EDs can serve as a safety net for vulnerable populations and can act as an access point for vaccination.